An automated algorithm for dating annually laminated sediments using X-ray radiographic images, with applications to Lake Van (Turkey), Lake Nautajarvi (Finland) and Byfjorden (Sweden) - Damcia, Emre; Cagataya, MNamik (Quaternary international, 2016)
Annually laminated (varved) sediments in marine and lake basins are important archives for paleoenvironmental and paleoclimatic reconstructions, especially with their property to provide a continuous chronology. In this study we introduce a new approach for counting laminae using both digital and analogue X-ray radiographic images. The requirement for the method is that the resolution of the image is higher than the minimum lamina thickness, so that the measurement interval should be at least one third of the minimum lamina thickness. In our method, 8-bit or 16-bit grey scale radiographic images are scaled to grey-scale values between 0 and 1, and every maximum and minimum peaks corresponding to seasonal lamination are defined along the sediment core. The algorithm counts laminae rather than varves, thus allowing control on estimation of more reliable age models. Detected peaks are summed cumulatively along the core length, using a step determined by the annual lamina number of the varve. Using the algorithm, we provide test examples from the varved sediments of the Lake Nautajarvi in Finland, Byfjorden in Sweden and Lake Van in eastern Turkey, and compare our results with previously dated levels in the cores. There are good agreements between the varve counting results of our study and the previous studies, except for the ages from the lower part of the Lake Van core corresponding to a time interval between ca. 7000 and 8000 BP, for which there is ca 1000 year difference between the two sets of results. This difference might be the result of under-counting of varves in the previous studies.